Digital multimedia perception and design - Ghinea, Gheorghita; Chen, Sherry Y. (Hershey, PA : Idea Group Pub., 2006)
"This book provides a well-rounded synopsis of the state-of-the-art in perceptual-based multimedia design"--Provided by publisher.
Includes bibliographical references and index.
Keywords: Multimedia systems; System design; Perception